Eigenmode analysis for turbomachinery applications - Moinier, P; Giles, M (2005)
The numerical computation of unsteady eigenmodes superimposed on an annular mean flow that is uniform axially and circumferentially, but nonuniform in the radial direction, is discussed. Both inviscid and viscous flows are considered, and attention is paid to the separation of the eigenmodes into acoustic, entropy, and vorticity modes. The numerical computations are validated by comparison to analytic test cases, and results are presented for more realistic engineering applications, showing the utility of the approach for postprocessing and for the construction of nonreflecting boundary conditions.